Internal Process Risk Management: A Proposed Conceptual Framework for Electronic Design Industry Process Gap - Gunalan SO Nadarajah; K.Kumar SO Balakrishnan (International Journal of Supply Chain Management, 2016)
Risk management is a crucial element in every industrys operational supply chain as the impact of turbulence in the form of uncertainty is drastic. Many researchers have published theories and frameworks defining Supply Chain Risk Management (SCRM) as there are gaps in the application definition gap, process gap, and methodology gap. This paper identifies the process gap in electronic design industry and proposes a modified framework adopted from Sodhi, Son and Tang (2012) to contribute in formulating a framework to define, operationalize and mitigate internal process supply chain risk management. The purpose of this paper is twofold. First, we categorize the detailed review with electronic design internal supply chain process. Second, we analyze and develop a framework with expected results upon completing the SCRM process throughout each internal process. Keywords Risk management, process gap, micro risk, uncertainty, supply chain risk management